Early single photon emission computed tomography in Sturge-Weber syndrome. Issue 5 (1st November 1997) - Pinton, F; Chiron, C; Enjolras, O; Motte, J; Syrota, A; Dulac, O
Abstract : OBJECTIVES: Functional cerebral imaging PET and SPECT have shown hypometabolism and hypoperfusion in the area of vascular malformation in children with epilepsy due to Sturge-Weber syndrome. However, data are scarce in infants and do not exist in patients with Sturge-Weber disease without epilepsy. The pattern of perfusion during the first two years of life was studied including patients before the onset of seizures. METHODS: Twenty two infants with later confirmed Sturge-Weber disease underwent SPECT examination using TOMOMATIC 564 (Medimatic) and xenon-133 at ages ranging from 8 days to 25 months. Twelve had never had seizures before SPECT and seven underwent a second SPECT a mean seven months later. Cerebral blood flow (CBF) was measured in the whole hemisphere and in the part of the cortex involved in the vascular malformation on both sides as well as a "pathological to normal" index for the hemisphere and vascular malformation. These values were compared with normal age paired values. RESULTS: Compared with controls, CBF and the indices in the hemisphere and vascular malformation were significantly decreased in patients who already had had seizures before SPECT, whereas they were significantly increased in 75% of the patients who had never had any seizures. On second SPECT, the indices were decreased in all patients, including the four who still remained non-epileptic. CONCLUSIONS: SPECT therefore detects CBF asymmetry in infants with Sturge-Weber disease, which tends to shift with age. The cortex involved in the vascular malformation is hyperperfused during the first year of life before first seizures. The classic hypoperfusion appears after one year of age, even in non-epileptic patients.